Principles of Quantitative Morphometric Assessment of Cholera Vaccines Safety - S. A. Bugorkova; T. V. Bugorkova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2011)
Worked out is the algorithm of cholera vaccines quality based on application of the methods of quantitative registration of formalized parameters which characterize pathologic and adaptive processes in the intestine of the immunized laboratory animals. The following parameters were selected as formalized ones: quantity of interepithelial lymphocytes, morpho-functional condition of apudocytes and scyphiform cells. Morphometric parameters are presented as associations of indicators in the form of indices and coefficients in order to carry out interrelated assessment of separate parts of homeostasis. It was determined that in case the assessed parameters were in the limits identified in corresponding controls, adaptation condition of the organism and alterations described in histological assay were considered as benign and characterized safety or efficiency of tested cholera vaccines.